Relationships between the Loch Ailsh and Borralan alkaline intrusions and thrusting in the Moine Thrust zone, southern Assynt culmination, NW Scotland - Searle, MP; Law, R; Dewey, J; Streule, M (Geological Society of London, 2010)
The Moine Thrust zone ofNWScotland marks the Caledonian orogenic front and in the Assynt region consists of several west-vergent major thrust sheets (Moine, Ben More, Glencoul and Sole Thrust sheets) that place allochthonous rocks onto the Lewisian basement and Torridon Group cover in the west. Here we present two new balanced and restored sections across the Moine Thrust zone in the region of the Loch Ailsh and Loch Borralan alkali intrusions. Syenites and alkaline pyroxenites intrude up to Durness Group carbonates. Syenites are interpreted as cut by the Moine and Ben More Thrusts and therefore their intrusion age (c. 430 Ma) provides a maximum age constraint on cessation of motion along the Moine Thrust. We review and discuss several controversies, notably: (1) relationships between folding in the Ben More Thrust sheet (Sgonnan Mor folds) and fabric development associated with intrusion of the Loch Ailsh pluton and initiation of the Moine and Ben More Thrusts; (2) structural relationships around the Borralan intrusion, particularly the nature of its basal and lateral margins (intrusive or thrust-ramp); (3) the structural relationships of the Cam Loch and Benn Fhuarain klippen; and (4) the timing of motion of all thrust sheets in the southern Assynt culmination. © The Geological Society of London 2010.